Response of Shallots (Allium Ascalonicum L.) To Azolla Pinnata Bokashi and NPK Fertilizer - Yusuf L Limbongan; Amelia A Limbongan (Journal of World Science, 2026)
Background: Shallot (Allium ascalonicum L.) is a high-value vegetable commodity in Indonesia, but its productivity remains low, particularly in North Toraja Regency. The use of organic fertilizers such as Azolla pinnata bokashi combined with inorganic NPK fertilizer offers potential for improving shallot growth and production through integrated nutrient management. Objective: This study aims to determine the response of shallot plants to the application of Azolla pinnata bokashi and NPK fertilizer. Method: A factorial experiment arranged in a randomized block design was conducted from May to August 2022. Treatments included three levels of A. pinnata bokashi (control, 30 tons/ha, 50 tons/ha) and three levels of NPK fertilizer (control, 250 kg/ha, 350 kg/ha). Data were analyzed using ANOVA and orthogonal polynomial methods. Results: The results showed that the application of 50 tons/ha A. pinnata bokashi gave the best results for all observed variables. The application of 350 kg/ha NPK fertilizer also produced the best growth and production. The interaction between 50 tons/ha A. pinnata bokashi and 350 kg/ha NPK fertilizer was the best combination treatment, significantly increasing plant height, number of bulbs, and bulb weight compared to other treatments. The response of shallot plants to the application of A. pinnata bokashi and NPK fertilizers was linear. Conclusion: The combination of 50 tons/ha A. pinnata bokashi and 350 kg/ha NPK fertilizer is recommended for optimizing shallot growth and production in highland areas. The integrated use of organic and inorganic fertilizers can improve shallot productivity through synergistic effects on plant growth parameters.